Does Extended Autonomy of Public Service Agency Lead to A Better Performance? A Case of Indonesian Community Health Centers - Rawung, Laura Catherine; Sholihin, Mahfud (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The aims of this study were: (1) to evaluate the performance of community health centers (Puskesmas) that implement PPK BLUD (Pola Pengelolaan Keuangan Badan Layanan Umum Daerah, a specific type of Financial Management of Local Public Service Agency); (2) to explore the factors affecting the performance of Puskesmas in implementing PPK BLUD; and (3) and to find out, if any, the benefits of the implementation of PPK BLUD. This study was conducted at seven Puskesmas that have implemented PPK BLUD in Balikpapan City, East Kalimantan, Indonesia. Performance in this study was evaluated using three aspects: financial aspects, service aspects, and overall benefits for the society. Design of the evaluation refered to Permendagri 61/2007 and Perdirjen Perbendaharaan Kementerian Keuangan No.PER-54/NT/2013, with several adjustments. Documents analysis and interviews were conducted to answer the research questions. The result showed an increase performance of Puskesmas after two and a half years implementation of PPK BLUD. The average performance of financial aspect was lower than the other two aspects. Puskesmas which have implemented PPK BLUD have better performance than the non-BLUDs Puskesmas. Factors that affected the performance of Puskesmas in implementing PPK BLUD were human resources, infrastructures, as well as support from health department, local government and the legislative board. Implementation of PPK BLUD allows Puskesmas to increase their revenue by improving their services, efficiency, and effectiveness.